LACUNARITY ANALYSIS OF CLIMATIC PHENOMENA IN THE STATE OF PERNAMBUCO - LUCENA, Leandro Ricardo Rodrigues de; STŎSÍC, Tatijana; CUNHA FILHO, Moacyr; DOS SANTOS, Carlos Renato (Brazilian Journal of Biometrics, 2016)
In this work we evaluate temporal variability of precipitation and temperature recorded at meteorological stations in the state of Pernambuco – Brazil during the period 01/01/2008 to 01/01/2011 using the one-dimensional lacunarity method. The results show that in the semi-arid "sertão" region in Pernambuco, temperature series demonstrate lower lacunarity values (indicating more homogeneous behavior) while precipitation demonstrates higher lacunarity values (indicating more heterogeneous behavior). It is shown that clustering of calculated lacunarity values can be used to identify geographical regions with characteristic temporal variability of precipitation and temperature and can contribute to planning of agricultural activities, development of strategies to reduce impact of extreme climatic phenomenon (drought), and ensure sustainable development of the region.